Proteção, prevenção e combate a incêndios aplicados em museus: um guia para o Museu Educativo Gama d’Eça e Victor Bersani - Blaya, Mariana Deboni (2017)
Through this work and the theoretical basement for the elaboration of a fire protection and prevention guide for museums, according to a case study at the Gama D'Eça and Victor Bersani Educational Museum linked to the Federal University of Santa Maria (UFSM). The guide was developed based on laws, regulations and technical resolutions aimed at directing strategies for the security of the visiting public, staff of servers and preservation of cultural heritage gathered in museums, in cases of accidents, specifically fires. The option for the theme reveals the importance of preservation of material and architectural patrimony, usually located in old, historical buildings, which can often even be overturned buildings, requiring special attention to the eminent risks that they are subject to. This research, besides addressing the fire prevention and its regulations, investigated the history of the building that houses the museum, Astrogildo de Azevedo palace, housed in a historic building, symbol of the eclectic architecture of Santa Maria in Rio Grande do Sul. Contextualize it in the contemporary scope of security and prevention of claims in order to guarantee the highest possible integrity and security of this patrimony in case of risk situations.